(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objectives- Pregnancy related lumbar and pelvic pain is very common. This pain is mainly because of hormonal and postural changes occur during pregnancy. Lumbar and pelvic pain is the most common cause of discomfort experienced by pregnant women during pregnancy. so, Awareness about therapeutic positions to reduce that pain is very necessary. Some ergonomic positions given to the women which can help to improve posture and decrease discomfort and also relieving pain. It will give more comfort to the patient for day to day activities during pregnancy. Hence, this study aims to aware the pregnant women about therapeutic positions , that decrease the lumbar and pelvic pain and discomfort. This study was conducted to find out the awareness of therapeutic positions in the pregnant women about lumbar and pelvic pain. Methodology- The study group consisted of 64 women. . Females with age group of 25 to 35yrs. A prevalence study was conducted among females of all three trimesters of pregnancy. Females were selected on the basis of inclusion and exclusion criteria. They were assessed by performing visual analog rating scale and questionnaire was used to evaluate any physical disability contribute to lumbar and pelvic pain.. The data was collected and analysed accordingly. Result- Data from sixty four females were obtained and analysed. Most of women were not aware about therapeutic positions ,only few were aware about therapeutic positions who was well educated. So 33% were aware and 67% were not aware about those positions. Following were some preferred therapeutic positions : 87% of women preferred side lying .8% preferred Quarter turn from prone, 3% preferred Sitting leaning forward, 2% preferred Sitting astride a chair. Conclusion- We found out that there is awareness about therapeutic position and there effects is not seen in all women during pregnancy in Krishna hospital , Karad.